COMPARISON TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION KINESIO TAPING AND DECREASING TO SCALE BACK PAIN IN PREGNANT WOMEN UNDER THIRD TRIMESTER IN PUBLIC HEALTH DISTRICT JUWIRING KLATEN, INDONESIA - Sri Wahyuni; Lilik Hartati; Novita P. Dewi; Jusmala Sari (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: The changes of soft tissues and connective buffer that able to decrease elasticity and flexibility of muscles can cause low back pain in the third trimester of pregnancy. Dissemination percentage of pregnancy low back pain at first trimester (16.7%), second trimester (31.3%), and third trimester (53%). It can cause long term back pain and increase the trend of back pain in post-partum and chronic back pain that can be more difficult to be cured, if the back pain is not handled well immediately. Management of low back pain can be done both by pharmacologically and non- pharmacologically. Aims: The present study aimed to compare the efficacy between transcutaneous electrical nerve stimulation (TENS) and Kinesio taping to the decreasing of low back pain on third trimester pregnant women in Public Health District Juwiring Klaten, Indonesia. Methods: This research is a quasi-experimental research with non-equivalent design and pretest and posttest control group design. There were 18 postpartum, selected by purposive sampling method, and divided into 2 groups equally – intellect TENS and Kinesio taping “Spol Kinematics Tex” group. The therapy was done for 6 times (twice a week). The pain was measured by NRS scale. Data was then analyzed by Wilcoxon and Mann-Whitney test to find the mean differences. Result: This research highlight that effectiveness of interact TENS to decrease low back pain on third trimester pregnant women then the application of Kinesio taping therapy (p value = 0,007) Conclusion: Transcutaneous Electrical Nerve Stimulation is more efficient to reduce low back pain scale in third-trimester of pregnancy compared to Kinesio taping. This present study suggests a promotion of ergonomics in the form of counseling and poster display to the public, especially pregnant women to reduce low back pain patient. Further research with a larger number of subjects with pure experiment is necessary to avoid the subjectivity factor measurements using a pain scale plasma levels of endorphins.